Beyond Functional Skills: A Systematic Review of Critical Digital Literacy in Vocational Teacher Education - Aditya Ramadhan Islami; Ade Gaffar Abdullah; Dadang Lukman Hakim; Isma Widiaty; Edy Purwanto; Miftahur Rizkiah; Aditya Ramadhan Islami; Ade Gaffar Abdullah; Dadang Lukman Hakim; Isma Widiaty; Edy Purwanto; Miftahur Rizkiah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The convergence of artificial intelligence, digitalization, and social media has exposed the insufficiency of functional digital literacy as an educational outcome, intensifying attention to Critical Digital Literacy (CDL) as a construct concerned with the ideological and structural logics of digital platforms rather than mere operational use. CDL scholarship nonetheless remains fragmented and lacks a stable, shared taxonomy of its dimensions. This study reports a systematic literature review, following the PRISMA 2020 protocol, of CDL in educational contexts. A Scopus search yielded 130 records, narrowed to 73 after automated screening and to 49 after a stringent CDL-focus eligibility criterion. Qualitative designs dominate the corpus (~55%), followed by conceptual work (~31%), while validated quantitative measurement remains rare (four studies). Inductive synthesis identifies eight recurring CDL dimensions, spanning critical-analytical, socio-political, ethical, identity-based, productive, and civic concerns. None of the 49 included studies directly addresses vocational (VET) teacher education, despite vocational teachers' need to combine technical fluency with critical disposition. Five gaps are identified, concerning measurement instruments, the functional-versus-critical divide, affective dimensions, institutional barriers, and generative AI, with future directions proposed. The synthesis is a necessary step toward a dedicated CDL framework for pre-service vocational teachers.